Collaborative Climate and Organizational Identification of Public Elementary School Teachers - Heidi E. Gumagay; Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between collaborative climate and organizational identification among public elementary school teachers. A descriptive-correlational research design was employed, with a 195 teachers from public elementary schools of San Roque District, Division of Davao City. Data were collected through standardized questionnaires and analyzed using mean, standard deviation (SD), Pearson product-moment correlation, and multiple linear regression. The findings revealed that both collaborative climate and organizational identification were at very extensive levels. Correlation analysis indicated a significant positive relationship between collaborative climate and organizational identification (r= 0.68, p < 0.05). Further analysis identified that among the dimensions of collaborative climate employee attitude, work group support, organizational culture, and immediate supervisor employee attitude had the strongest influence on organizational identification (r= 0.70, p < 0.05). Based on these findings, it is recommended that school administrators implement leadership development programs, recognition initiatives, and collaborative professional development activities to enhance teacher engagement and institutional commitment. Strengthening these dimensions may further improve educators’ connection with their schools, fostering a more cohesive and motivated teaching workforce.